Equity valuation of Grieg Seafood ASA - Olsen, Charlotte Solberg (2024)
Through a combination of intrinsic valuation and relative valuation, this thesis estimates Grieg Seafood ASA’s equity value as of May 6, 2024, and provides an estimated target price along with a final stock recommendation. By using a traditional DCF model and peer multiples, this thesis determines a target price of NOK 86.51 per share for Grieg Seafood, with a 50% weighting between the two approaches to capture both the company's business performance and the market's cyclicality. Despite historical challenges, such as lower margins compared to peers and liquidity risks, strategic investments in post-smolt initiatives, and successful harvests in Newfoundland in 2023, total harvest volume and margins are expected to increase over the next five years. Based on the DCF valuation, a target price of NOK 66.05 is estimated. However, the relative valuation suggests an implied share price of NOK 106.98. With a 50% weighting between the two approaches and the current share price of NOK 70.45 (as of May 6, 2024), this analysis suggests that the stock is undervalued. Therefore, a buy recommendation is provided. Através de uma combinação de avaliação intrínseca e avaliação relativa, esta tese estima o valor patrimonial e preço-alvo da Grieg Seafood ASA a 6 de maio de 2024, e elabora uma recomendação final de ações. Utilizando um modelo tradicional de DCF e múltiplos de pares, esta tese determina um preço-alvo de NOK 86,51 por ação para a Grieg Seafood, com um peso de 50% entre as duas abordagens para capturar tanto o desempenho da empresa quanto os ciclos do mercado. Apesar dos desafios históricos, como margens mais baixas em comparação com os pares e riscos de liquidez, investimentos estratégicos em iniciativas de pós-smolt e colheitas bem sucedidas nas operações de Newfoundland em 2023, o volume total de colheita e as margens devem aumentar nos próximos cinco anos. Com base na avaliação DCF, um preço-alvo de NOK 66,05 é estimado. No entanto, a avaliação relativa sugere um preço implícito de NOK 106,98 por ação. Com um ...